2021
DOI: 10.3390/biomedicines9101460
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles and Prognostic Value of FABPs in Colorectal Adenocarcinomas

Abstract: Colorectal cancer (CRC) is one of the world’s leading causes of cancer-related deaths; thus, it is important to detect it as early as possible. Obesity is thought to be linked to a large rise in the CRC incidence as a result of bad dietary choices, such as a high intake of animal fats. Fatty acid-binding proteins (FABPs) are a set of molecules that coordinate intracellular lipid responses and are highly associated with metabolism and inflammatory pathways. There are nine types of FABP genes that have been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 108 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…FABPs can promote fatty acid transport to particular intracellular organelles for transcription modulation in the nucleus, lipid oxidation in peroxisomes or mitochondria, storage as lipid droplets and enzyme activity modulation in the cytoplasm and membrane synthesis, signaling and trafficking in endoplasmic reticulum [21]. As a FABP, FABP6 is overexpressed in CRC tissues and is a potentially promising treatment target for CRC [22]. A former study suggested that downregulating FABP6 in CRC cells depresses tumor development and growth [23].…”
Section: Discussionmentioning
confidence: 99%
“…FABPs can promote fatty acid transport to particular intracellular organelles for transcription modulation in the nucleus, lipid oxidation in peroxisomes or mitochondria, storage as lipid droplets and enzyme activity modulation in the cytoplasm and membrane synthesis, signaling and trafficking in endoplasmic reticulum [21]. As a FABP, FABP6 is overexpressed in CRC tissues and is a potentially promising treatment target for CRC [22]. A former study suggested that downregulating FABP6 in CRC cells depresses tumor development and growth [23].…”
Section: Discussionmentioning
confidence: 99%
“…FABP genes expression in human CRC was studied. Prayugo et al reported that numerous FABP genes are altered in CRC patients, and that FABP6 could be a potential biomarker of colorectal adenocarcinomas ( Prayugo et al, 2021 ). Bile acids that are increased in colon adenomas and cause DNA damage and apoptosis in colonic epithelium are thought to be responsible of the raised FABP6 expression in early-stage carcinogenesis in CRC ( Imray et al, 1992 ; Fujii et al, 1993 ).…”
Section: The Fatty Acids (Fas) Overview: From Biochemistry To Metabolismmentioning
confidence: 99%
“…In addition, the levels of FABP6 mRNA were found to be higher in HCCs than in adjacent normal liver tissues [22]. FABP1 and FABP6 are strongly expressed in colorectal cancer tissues, with overexpression of FABP6 protein was found to be associated with poorer overall survival (OS) in colorectal cancer patients [23]. The levels of FABP9 was found to be higher in breast cancer samples than in adjacent normal breast tissues [24].…”
Section: Introductionmentioning
confidence: 99%